Comparison between a commercial blend of functional oils and monensin on the performance and microbiota of coccidiosis-challenged broilers - Moraes, P. O.; Cardinal, K. M.; Gouvea, F. L.; Schroeder, B.; Ceron, M. S.; Lunedo, R. [UNESP]; Frazzon, A. P. G.; Frazzon, J.; Ribeiro, A. M. L. (Oxford Univ Press, 2019)
The aim of the study was to evaluate the effects of a cashew nut shell oil and commercial castor oil blend (CNSL-Castor oil) on the performance and microbiota of broiler chickens with and without coccidiosis challenge. A total of 864 one-day-old male chicks (Cobb) were randomly distributed to receive 6 treatments (8 pens/treatment; 18 chicks/pen) in a 3 x 2 factorial, with 3 additives (control [non-additives], 100 ppm sodium monensin, or 0.15% CNSL-Castor oil blend), and 2 levels of coccidiosis challenge at 14 D of age (unchallenged or inoculated by gavage with 1 mL of solution containing oocysts sporulated with Eimeria tenella, Eimeria acervulina, and Eimeria maxima). No differences in productive performance were observed among treatments in the pre-challenge period and in unchallenged birds (P > 0.05). Seven-days post-challenge, birds receiving monensin performed better than birds in the positive control group (non-additive and challenge) or in the CNSL-Castor oil group (P > 0.05). However, 14 D post-challenge, birds supplemented with CNSL-Castor oil presented higher weight gain and better feed conversion (P > 0.05), without any change in feed intake (P > 0.05). During the accumulated period (1 to 42 D of age), the live weight, weight gain, and feed intake did not differ between the CNSL-Castor oil and monensin groups, both of which presented higher values than the positive control. Lactobacillus spp. and Clostridium perfringens numbers were increased in the challenged birds (P < 0.05). CNSL-Castor oil supplementation reduced Clostridium cluster XIV, C. perfringens, and S. aureus, compared with the monensin and control groups (P > 0.05). In addition, the CNSL-Castor oil group presented the highest number of Lactobacillus spp. copies, followed by the monensin and positive control groups (P > 0.05). Thus, monensin and CNSL-Castor oil effectively minimized the impact of coccidiosis at different times. While monensin acts as an antimicrobial, CNSL-Castor oil modulates the intestinal microbiota with antimicrobial action against gram-positive bacteria, mainly C. perfringens and S. aureus.
Keywords: Coccidiosis; functional oil; gut health; microbiota; monensin